Development and optimization of 3D printable cementitious composites for printing applications - Weng, Yiwei (Nanyang Technological University, 2020)
3D concrete printing (3DCP) builds up objectives in a layer-atop-layer manner and has attracted much attention recently due to many advantages, such as customized production, reduced waste, and diminished lead-time of the rapid prototype. A number of works have been conducted in 3DCP in recent years. However, limitations remain in 3DCP, especially in the field of developing consistent and reliable cementitious materials for 3DCP.